Morphometric study of the postnatal growth of the parotid gland of the mouse - de Castro Ribeiro, Tiago Turri; Sottovia, André Dotto [UNESP]; Cestari, Tania Mary; Taga, Rumio (FapUNIFESP (SciELO), 2006)
The growth of the mouse parotid glands during 7 and 35 days of postnatal life was studied by morphometric methods. The mass of the gland, the volume of each morphological compartment, and the cell number in each compartment were evaluated. The data obtained for each evaluated dimension were adjusted by an exponential equation, of the type Y = a.e KX, thus permitting the calculation of their mean duplication time (T D), i.e., an estimation of their growth rate. Analysis of the results showed a marked 1,424% increase in the gland mass during the whole studied period, with T D = 7.10 days. This growth occurred by increases in absolute volume of acini, intercalated ducts, striated ducts, excretory ducts and stroma, with percentual increases of 3,048%, 417%, 2,662%, 2,594% and 367%, respectively, and T Ds of 5.62, 11.71, 5.55, 5.47 and 14.45 days, respectively. Analysis of the cell number growth in each compartment showed increases of 1,904%, 285%, 1,228%, 1,090% and 286%, respectively, and T Ds of 6.62, 20.40, 7.19, 7.26 and 14.51 days, respectively. Based on the present results, we concluded that the growth of the mouse parotid glands from day 7 to day 35 of age occurred by intense cell accumulation, mainly in the acini, striated ducts and excretory ducts, with a growth rate sensibly higher than that of the intercalated ducts and stroma.
Keywords: Animals; Growth and embryonic development; Histology; Parotid gland; Regression analysis; analysis of variance; animal; cell count; cell size; comparative study; cytology; growth, development and aging; male; mouse; parotid gland; regression analysis; Analysis of Variance; Cell Count; Cell Size; Male; Mice; Parotid Gland; Regression Analysis